When Posting About Products on Social Media Backfires: The Negative Effects of Consumer Identity Signaling on Product Interest - Grewal, Lauren; Stephen, Andrew T.; Coleman, Nicole Verrochi (Journal of Marketing Research, 2019)
Consumers frequently express themselves by posting about products on social media. Because consumers can use physical products to signal their identities, posting about products on social media may be a way for consumers to virtually signal identity. The authors propose that there are conditions in which this action can paradoxically reduce a consumer’s subsequent purchase intentions. Five experiments demonstrate that posting products on social media that are framed as being identity-relevant can reduce a consumer’s subsequent purchase intentions for the same and similar products, as this action allows consumers to virtually signal their identity, fulfilling identity-signaling needs. Fortunately for retailers, the authors suggest theoretically and managerially relevant moderators that attenuate this negative effect on intent to purchase. These findings have important implications for how firms can conduct social media marketing to minimize negative purchase outcomes.